Natural luteolin from methanolic extract of Malaysian brucea javanica leaves induces apoptosis in hela cell lines - Ismail, Norzila; Shajarahtunnur, J; Hasmah, A (School of Health Sciences, Universiti Sains Malaysia, 2016)
There are a growing number of deaths of cancer patients due to toxicity of conventional chemotherapy. Therefore, continuous discovery of natural anticancer compounds with cytoselective actions would be an ideal strategy to overcome the problem. Thus, natural products from plant are still the alternative source in the search for anticancer drugs that can have a direct effect on both cancer cell removal and also minimize the side effects to the patients. Based on the traditional usage and pharmaceutical potential of Brucea javanica reported before, a study on the leaves of this plant was carried out. The aims of the study were to isolate the bioactive compound from B. javanica Leaves (BJL) extracts via bioassay-guided fractionation using several selected cancer cell lines, to determine the mode of cancer cell death induced by BJL’s active compound and the molecular mechanism of apoptosis implicated in cancer cell lines by measuring the level of apoptotic protein expression such as bax, bcl-XL, caspase-3 and tumour suppressor p53. Among three crude extracts of BJL, methanol was the most potent against selected cancer cell lines which consist of cervical, breast, bone, ovarian and liver cancer cells. Cisplatin was used as positive control for the antiproliferative assay. Using a bioassay-guided fractionation, chromatography, NMR and mass spectrometry analysis we have isolated luteolin. It is a known compound from the flavonoid group which was found to be cytoselective. The IC50 value for HeLa is 8.02 μg/ml while for Vero is >99 μg/ml. Hoechst 33258 staining and flow cytometric analysis of Annexin V-FITC staining revealed that luteolin induces apoptotic cell death in cervicalcancer cell HeLa. Flow cytometric analysis also showed that luteolin induces apoptosis by increasing the p53, bax and caspase-3 protein expression.